(untitled) (International Journal of Food and Nutritional Sciences, 2023)
This study aims to explore the level of moral values among high school students in Krishna District, Andhra Pradesh. With increasing concerns about the erosion of values in modern society, especially among the youth, the study investigates how moral values vary with respect to gender, locality (rural/urban), and type of school